Design and Construction of Special Service Tools for Forklift Wheel Bearings Lubrication Using a Pneumatic System - Krisna Hadiyanto; Yasya Khalif Perdana Saleh; M. Untung Zaenal Priyadi (Integrated Mechanical Engineering Journal, 2026)
Manual lubrication of forklift wheel bearings is still inefficient and inconsistent. This study aims to design and test a pneumatic-based bearing lubrication aid to improve lubrication efficiency and speed. The research method used is experimental, involving tool design and testing with air pressure variations of 2, 3, and 4 bar on bearing types 30306, 32206, and 32207. The observed parameters include lubrication time and the amount of grease supplied. The results show that increasing air pressure shortens lubrication time but reduces the amount of grease delivered. An air pressure of 3 bar is considered the most optimal condition as it provides a balance between lubrication speed and grease adequacy. Therefore, the pneumatic system is proven effective in improving the lubrication performance of forklift wheel bearings